Activities of the Ta'lim and Istighotsah Assembly at the Islamic Boarding School Sunan Kalijaga Batu City as an Instrument of Religious Transformation at the Bantengan Arts Activists Community - Shofiyulloh, Muhammad; Ulum, Mohammad Samsul; Parmujianto, Parmujianto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This article investigates the role of religious activities, particularly istighotsah and majelis ta’lim, in shaping and transforming the religious consciousness of the traditional Bantengan art community in Karangmloko, Batu City. Employing a descriptive qualitative approach, the study utilizes indepth interviews, participatory observation, and documentation. The findings reveal that regular religious activities organized by Pondok Pesantren Sunan Kalijaga promote positive changes in the understanding and practice of Islamic values among the local community. These activities serve as effective dakwah tools by adaptively and inclusively incorporating local cultural elements, thereby reinforcing religious identity while preserving cultural values.